Perancangan Artbook Storytelling Astrologi Tiongkok untuk Anak-Anak - Meindanu Dimas Prasetyo; Aditya Nirwana; Didit Prasetyo Nugroho (Citradirga : Jurnal Desain Komunikasi Visual dan Intermedia, 2020)
At present, specifically millennial generation, both children and teenagers in Indonesia are more familiar with the popularity of western-style astrology than Chinese astrology. Chinese astrology is assumed with ancient and boring things. That is because the way how to present eastern astrological merely informative content, such as history books, eastern astrological knowledge, etc. without containing of visual storytelling content. For this reason, there is an alternative media solution to solve these problems, named "Designing Chinese Astrological Storytelling Artbooks for Children". The method used is non-metric (qualitative). Qualitative data obtained from literature studies, observations, and interviews. The outputs are two-dimensional illustrations of the Twelve Chinese Astrology's Artbook.